The inequality in women's work: Sketching philosophies - Bravo Montalvo, Washington Luis (2023)
From the understanding of work as a human activity, the first impression we get of the idea of "equality at work" is that there is no equality at work. In fact, we count examples of them as theories trying to explain work as degradation; One of them is inequality in the work of Women, an area in which history has great responsibility, which has presented it to us, almost always, playing its traditional role: As subordinate, at home, subject to culturally accepted hierarchies. Perhaps, the answer as to why, could be delving into the same threshold where it all began, where inequality began to originate: The mentality that we believed to be correct and from which we feed through the education we receive.